Pneumococcal Vaccination Coverage Among Adults at Risk in the Russian Federation - V. A. Korshunov; N. I. Briko; R. V. Polibin; A. N. Plutnitsky; I. B. Kulikova; N. D. Pakskina; D. D. Khlebnova (Эпидемиология и вакцинопрофилактика)
Relevance. Pneumococcal infection remains one of the most significant health problems worldwide. Vaccination of adults against it has been carried out in the Russian Federation for over 10 years. During this time, more than 9 million people have been vaccinated. However, data on the level of coverage among adults of certain risk categories are not routinely collected. Our study in 2019 showed that it was low in most groups. Given the significant increase in the volume of vaccination over the past five years, it seems appropriate to conduct a study to assess changes in the level of coverage.Aim. To study the level of vaccination coverage against pneumococcal infection in adult risk groups in the Russian Federation.Materials and methods. An observational descriptive retrospective epidemiological study was conducted. Information on the number and contingents of people vaccinated against pneumococcal infection was collected by sending a request to the executive authorities of the constituent entities of the Russian Federation in the field of healthcare. The depth of data collection was 8 years (from 2015 to 2023 inclusive), information was received from 74 out of 89 regions. In addition, federal statistical observation forms were used: No. 5 «Information on preventive vaccinations» and No. 6 «Information on the contingents of children and adults vaccinated against infectious diseases», data from the Unified Interdepartmental Information and Statistical System. The results obtained were compared with the indicators obtained in the 2019 study, which was conducted according to a similar design. The analysis was carried out using descriptive statistics methods.Results. The coverage rate of vaccination against pneumococcal infection among the adult population in the Russian Federation increased from 1.5% in 2018 to 7.7% in 2023. The most significant coverage rates were achieved among persons subject to conscription for military service (78.5%) and persons over 60 years old, living in residential care facilities (87.7%). By 2023, vaccination coverage has increased among the following risk categories: individuals with chronic bronchopulmonary diseases (from 15.1% in 2018 to 47.9% in 2023), chronic heart diseases (from 3.8% to 17.0%), patients with endocrine diseases (from 1.1% to 17.6%), liver diseases (from 4.0% to 12.0%), healthcare workers (from 4.9% to 19.7%), school and preschool employees (from 3.1% to 12.9%), employees of residential care facilities (homes for elderly, nursing homes, ect.) (from 0.1% to 26.9%), the elderly population as a whole (from 1.4% to 12.7%), and working-age men (from 1.4% to 7.0%). There was virtually no increase in coverage among all groups of immunocompromised patients (1.0% in 2018, 6.2% in 2023), the working population with risk factors harmful to the respiratory system (0.9% in 2018, 5.0% in 2023), workers in the oil and gas and chemical industries (1.3% in 2018, 1.8% in 2023).Conclusion. The obtained results indicate the need to develop a strategy of measures to promote increased vaccination coverage in risk groups that are insufficiently covered by vaccination against pneumococcal infection.